1970
DOI: 10.3329/bjar.v34i3.3962
|View full text |Cite
|
Sign up to set email alerts
|

Study on phenology and yielding ability of Basmati fine rice genotypes as influenced by planting date in <i>aman</i> season

Abstract: The experiment was conducted at the Bangladesh Rice Research Institute Farm, Gazipur in Aman season to determine the optimum time of planting and to find out the genotypes having high yield potential. Fine rice genotypes Basmati PNR, Basmati 370, Basmati 375, and Basmati-D were transplanted from 22 July and continued upto 7 October at an interval of 15 days both in 1999 and 2000. Thirty-day old seedlings were transplanted at a spacing of 20 cm x 15 cm. The tallest plant was found in the early-planted crop at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
6
9
0
Order By: Relevance
“…Rice plants sown on the second or third dates significantly produced greater panicle number m -2 than those sown on early and late dates in the two seasons. These findings are consistent with those reported by Lee and Jun (1998), Ganajaxi et al (2001), Linscombe et al (2004), Singh et al (2004), Nahar et al (2009) and Mannan et al (2009).…”
Section: -7-number Of Panicle M -2supporting
confidence: 93%
See 2 more Smart Citations
“…Rice plants sown on the second or third dates significantly produced greater panicle number m -2 than those sown on early and late dates in the two seasons. These findings are consistent with those reported by Lee and Jun (1998), Ganajaxi et al (2001), Linscombe et al (2004), Singh et al (2004), Nahar et al (2009) and Mannan et al (2009).…”
Section: -7-number Of Panicle M -2supporting
confidence: 93%
“…Rice plants sown on the second or third dates produced greater tillers numbers m -2 than those sown on early and late dates in the two seasons. These finding are supported by the work done by Aslam (2000), Dixit et al (2004), Akram et al (2007), and Mannan et al (2009).…”
Section: -4-number Of Tillers M -2supporting
confidence: 70%
See 1 more Smart Citation
“…Minimum 1000-grains weight was recorded for V 3 (19.83 g) in CM that was statistically similar with V 2 (20.67 g) and V 3 (19.69 g) in SRI (Table 1). Mannan et al (2009) also opined that heavier grain weight was found in early planted crop and grain weight decreased with the delayed transplanting.…”
Section: Weight Of 1000mentioning
confidence: 97%
“…However, this study concludes with the need of a legislation control in the cycle of sowing to make it effective. On the other hand, dependence of yield with the sowing date is shown in [12] and [18], so the knowledge of sowing dates can be used to establish when is the optimum date to plant in certain area.…”
Section: Introductionmentioning
confidence: 99%